Broken debris on the southeast face of the adhisthana - Temples of India Project Team (Jio Institute, 2024)
Broken debris from the original temple assembled on the southeast face of the adhisthana. Additionally, U-shaped rounded stones are placed on the parapet, although their original position or purpose is unknown). Broken debris from the original temple assembled on the southeast face of the adhisthana. Additionally, U-shaped rounded stones are placed on the parapet, although their original position or purpose is unknown). Pradakshina along the east side of the adhisthana. The pradakshina has been paved with stone by the Archaeological Survey of India (ASI).